2019
DOI: 10.2214/ajr.18.20090
|View full text |Cite
|
Sign up to set email alerts
|

MR Arthrogram Features That Can Be Used to Distinguish Between True Inferior Glenohumeral Ligament Complex Tears and Iatrogenic Extravasation

Abstract: A vulsion of the inferior glenohumeral ligament (IGHL) from its insertion on the medial humeral neck, otherwise known as the humeral avulsion of the glenohumeral ligament (HAGL) lesion, has a frequency of up to 9% in patients with glenohumeral instability [1-3]. Unfortunately, this diagnosis may be missed at both clinical examination and routine MRI interpretation. Detection is important, because arthroscopic or open surgical repair of HAGL lesions is associated with good clinical outcomes and lower recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…As reported in the literature, a number of signs can be useful to make this distinction. 6 In our experience, a true capsular lesion can often be diagnosed at the time of contrast injection under fluoroscopy. A true capsular avulsion will show leakage immediately.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…As reported in the literature, a number of signs can be useful to make this distinction. 6 In our experience, a true capsular lesion can often be diagnosed at the time of contrast injection under fluoroscopy. A true capsular avulsion will show leakage immediately.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study describes a method to differentiate iatrogenic leakage from a true axillary ligament lesion. 6 Because contrast leakage can present a diagnostic dilemma and potentially have a negative impact on image quality, we decided to target the cause of leakage and a potential solution in this study (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three discordant cases in this series illustrated the importance of critically scrutinizing subtle findings detected on MR arthorgrams to not overcall the injury. Other considerations of note have been explored by Wang et al 24 pertaining to true and false positive MR arthrograms with respect to IGHL integrity. Specifically, they reported that isolated extravasation of contrast from the posterior portion of the axillary pouch of the IGHL was seen only in cases of iatrogenic extravasation and never identified with a true tear.…”
Section: Discussionmentioning
confidence: 99%
“…MR arthrography is particularly helpful, but iatrogenic extravasation of contrast material can be mistaken for an inferior glenohumeral ligament tear. The findings of a torn anterior band, a thickened ligament (> 3 mm), reverse-tapered calibre, and scarred appearance of the torn margins suggest a tear, while isolated disruption of the posterior axillary pouch is found in iatrogenic extravasation [ 68 ]. Posterior HAGL may also occur during a shoulder dislocation, where contrast may dissect through a defect in the posterior band of the inferior glenohumeral ligament [ 69 ] ( Figure 18 ).…”
Section: Glenohumeral Instabilitymentioning
confidence: 99%